Exercise as a mean to reverse the detrimental effect of high-fat diet on bone’s fracture characteristics (Fracture and Structural Integrity, 2017)
The aim of this study is to investigate whether exercise can reverse some of the adverse effects of high-fat-diet-induced obesity on lipid metabolism and bone biomechanical properties. A total of 26 adult male C57bl/6J mice were randomly assigned into three groups: (A) Control group (n=6), (B) High-fat diet group (n=10), (C) High-fat diet and exercise group (n=10). Body mass and relevant biochemical parameters were measured for the duration of the experimental protocol (37 weeks). Mechanical strength of both femurs of each animal was assessed in-vitro based on three point bending tests. It was revealed that exposure to high-fat diet led to significant increase of body mass and cholesterol levels and also to substantial changes in bone morphology and strength. Ultimate stress for the animals exposed to high-fat diet and those exposed to high-fat-diet and exercise was 25% and 24% lower compared to control, respectively. Exercise increased bone thickness by 15% compared to animals that were not exposed to exercise. It was concluded that high-fat-diet appears to have a detrimental effect on bone biomechanics and strength. Exercise reversed the reduction in bone thickness that appears to be induced by high-fat diet. However no statistically significant increase in bone strength was observed.
Keywords: Bone biomechanics; Mice; Femur; High-fat-diet; Three-point bending; Bending strength